2004
DOI: 10.1007/s10038-004-0150-7
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the prion protein gene (PRNP) in a Korean population

Abstract: Human prion protein gene (PRNP) has been considered to be involved in the susceptibility of humans to prion diseases. Polymorphisms of methionine (Met)/ valine (Val) at codon 129 and of glutamic acid (Glu)/ lysine (Lys) at codon 219 are thought to play an important role in susceptibility to sporadic, iatrogenic and variant Creutzfeldt-Jakob disease (CJD). Although the genotype distribution of polymorphisms in PRNP open reading frame (ORF) has been reported in many European populations, among Asian groups, it h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 21 publications
(43 reference statements)
0
56
0
Order By: Relevance
“…Since ethnic background strongly influences on the M129V polymorphism and the genetic susceptibility to AD, further evaluation of the data from East Asians and across ethnic groups will solve the controversial issues of a genetic role of PRNP in AD and cognitive decline in the elderly. The frequencies of the EE genotype and of the E allele at codon 219 were significantly higher in the Korean population than the Japanese population (Jeong et al, 2004). The 219 polymorphism was not associated with AD in Korean population regardless of the age of onset or ApoE-4 status as seen in Japanese population (Ohkubu et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since ethnic background strongly influences on the M129V polymorphism and the genetic susceptibility to AD, further evaluation of the data from East Asians and across ethnic groups will solve the controversial issues of a genetic role of PRNP in AD and cognitive decline in the elderly. The frequencies of the EE genotype and of the E allele at codon 219 were significantly higher in the Korean population than the Japanese population (Jeong et al, 2004). The 219 polymorphism was not associated with AD in Korean population regardless of the age of onset or ApoE-4 status as seen in Japanese population (Ohkubu et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…The M allele frequency is highest in Central and East Asia (> 90%), high in the Pacific (approximately 81%), in Europe (57-75%) and low (approximately 30%) in Native Americans (Palmer, ApoE-4 (-) (n = 306) ApoE-4 (+) (n = 181) 1991; Soldevila et al, 2003;Jeong et al, 2004;Yu et al, 2004;Lucotte and Mercier, 2005). Similarly, the MM genotype is highly abundant (> 93%) in East Asia.…”
Section: Discussionmentioning
confidence: 99%
“…79,80 First and foremost among these is a polymorphism at PRNP codon 129 between methionine and valine, which has a strong disease susceptibility and phenotype modifying effect. 81 There are marked differences in codon 129 allele frequency worldwide: in the UK and Northern European population, the 129M allele frequency is around 0.65 with a slightly increasing cline through Europe into Africa 79,82 and a marked increasing cline through Asia, 67,83,84 129V is rare in Japan. 129V is the more frequent PRNP allele in only two regions: the Eastern Highlands of Papua New Guinea (PNG) at 0.55, and some Native American populations.…”
Section: Prnp Polymorphisms and Prion Disease Susceptibilitymentioning
confidence: 99%
“…Possibility of Koreans developing vCJD: According to a recent study [8], Korean people's genome type showed a MET/MET genotype frequency of 94.33% at Codon 129. This means that the risk of getting infected with vCJD is higher than the Japanese (93%) and about 3 times higher than the English people (36.79%).…”
Section: Analysis Of Handling Of Dead Animalsmentioning
confidence: 99%